Factors Affecting Career Choice Decisions among Adolescents in Jalandhar city - Batra, Roopali; Kalia, Ashima (Gyan Management Journal, 2013)
Choosing the perfect career can dramatically increase happiness, self-confidence, and productivity in one's life. This decision will have an impact on an individual, throughout his or her life. From earlier times, career has always been important but with the passage of time,factors affecting the same like, gender gap to parental influences have been witnessing a change. The present study carried out on 100 adolescents, interviewed with the help of a pre-structured questionnaire, aims at finding out the underlying & cognitive factors thatgovem adolescents mind while making a career choice decision and further in choosing an appropriate educational institute to pursue the career. The study also provides a considerable insight into the different aspects of career choice decision like sources of information and impact of reference groups in steering students towards their career path. It further explores the impact of demographic variables of Gender and parental ocwpation on career aspirations.
Keywords: Career Choice; Factors; Educational fnstitutes; Job Related Factors; Reference Groups; Media; Gender; Parental Occupation